Omega‐3 PUFA supplementation and the response to evoked endotoxemia in healthy volunteers. Issue 3 (5th November 2013) - Ferguson, Jane F.; Mulvey, Claire K.; Patel, Parth N.; Shah, Rhia Y.; Doveikis, Julia; Zhang, Weiyu; Tabita‐Martinez, Jennifer; Terembula, Karen; Eiden, Michael; Koulman, Albert; Griffin, Julian L.; Mehta, Nehal N.; et al.
<x xml:space="preserve">Abstract</x> Scope Fish oil‐derived n‐3 PUFA may improve cardiometabolic health through modulation of innate immunity. However, findings in clinical studies are conflicting. We hypothesized that n‐3 PUFA supplementation would dose‐dependently reduce the systemic inflammatory response to experimental endotoxemia in healthy humans. Methods and results The Fenofibrate and omega‐3 Fatty Acid Modulation of Endotoxemia (FFAME) study was an 8‐wk randomized double‐blind trial of placebo or n‐3 PUFA supplementation (Lovaza 465 mg eicosapentaenoic acid (EPA) + 375 mg docosahexaenoic acid (DHA)) at "low" (1/day, 900 mg) or "high" (4/day, 3600 mg) dose in healthy individuals (N = 60; age 18–45; BMI 18–30; 43% female; 65% European‐, 20% African‐, 15% Asian‐ancestry) before a low‐dose endotoxin challenge (LPS 0.6 ng/kg intravenous bolus). The endotoxemia‐induced temperature increase was significantly reduced with high‐dose (p = 0.03) but not low‐dose EPA + DHA compared to placebo. Although there was no statistically significant impact of EPA + DHA on individual inflammatory responses (tumor necrosis factor‐α (TNF‐α), IL‐6, monocyte chemotactic protein (MCP‐1), IL‐1 receptor agonist (IL‐1RA), IL‐10, C‐reactive protein (CRP), serum amyloid A (SAA)), there was a pattern of lower responses across all biomarkers with high‐dose (nine of nine observed), but not low‐dose EPA + DHA. Conclusion EPA + DHA at 3600 mg/day, but not 900 mg/day, reduced fever and had a pattern of attenuated LPS induction of plasma inflammatory markers during endotoxemia. Clinically and nutritionally relevant long‐chain n‐3 PUFA regimens may have specific, dose‐dependent, anti‐inflammatory actions.